Participação: uma contribuição para a universidade - Pigatto, Giuliana Aparecida Santini [UNESP]; Simon, Maria Isolda Wagner [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
The participation of students in the University activities is extremely important. In aiming at that, the Tupã Differentiated Unit developed a research among students of the Business and Agribusiness Administration course to find out which were the expectations they have in relation to the course and what they know about it. It was found that students have good expectations in relation either to the course and the University. Their choices were conscious, although they do not have a clear view of the professional field. The University, aiming at an integrated action with its students and allowing them opportunities of growth, will deal with this issue.

É extremamente importante a participação dos estudantes em atividades da Universidade. Visando a esse objetivo, a Unidade Diferenciada de Tupã realizou uma pesquisa com os estudantes do curso de Administração de Empresas e Agronegócios. Constatou-se que os alunos possuem boas expectativas com relação ao curso e também à Universidade. Suas escolhas foram conscientes, no entanto, não têm total clareza sobre a atuação de um profissional na área. Essa questão será trabalhada pela Universidade, para uma ação integrada com seus alunos, proporcionando-lhes oportunidades de crescimento.
Participation: a contribution to the university
Keywords: Participation; Institution; Expectations; Humanas; Educação; Participação; Instituição; Expectativas